Program "Jari Peri" Untuk Meningkatkan Keterampilan Dan Efikasi Mengajar Prevensi Kekerasan Seksual Pada Anak (KSA) - Wahida, Dina; Paramastri, Ira (Journal of Psychological Perspective, 2020)
Kekerasan seksual pada anak (KSA) merupakan pemaksaan atau ancaman seorang anak dalam aktivitas seksual yang dilakukan orang dewasa atau teman sebaya. Kekerasan seksual tidak hanya terjadi dikalangan anak-anak pada umumnya namun juga terjadi pada anak yang berkebutuhan khusus, karena mereka belum dapat mengenal dengan baik organ vital yang harus dilindungi (misal vagina, payudara, penis, dan pantat). Hal tersebut dapat menjadikan trauma baik fisik, psikologis maupun sosial. Ironisnya kejadian ini tidak selalu terlaporkan baik kepada pihak yang berwenang ataupun lembaga perlindungan anak. Agar kejadian ini tidak semakin meningkat, maka dibutuhkan suatu strategi prevensi primer. Penelitian ini bertujuan untuk mengetahui apakah progam Jari Peri (guru ajari perlindungan diri) dapat meningkatkan keterampilan dan efikasi mengajarkan prevensi KSA. Penelitian ini menggunakan metode kuantitatif dengan rancangan eksperimen kuasi the untreated control group design with multiple dependent pretest and posttest. Uji statistik menggunakan mixed design ANOVA. Skala efikasi digunakan untuk mengetahui peningkatan efikasi mengajar guru, cheklis keterampilan komunikasi.  Abstract: The child sexual abuse (CSA) is coercion or threat of a child in sexual activity of adults or the opposite sex of peers. The sexual abuse is not only occurred among children in general, but also occurred in children with special needs, because they do not familiar with the vital organs that should be protected (e. g vagina, breast, penis, and buttocks). This is able to make a trauma, either physical, psychological or social. Ironically, this incident is not always reported to the authorities or child protection agencies. For this incident does not increase, it needs to take a strategy primary prevention. The purpose of this study is to determine how effective the program of "Jari Peri" (the teachers teach self-protection) to improve skills and teacher's efficacy for the prevention of child sexual abuse. The method used in this study was a quantitative method with quasi-experimental; untreated control group design with multiple dependent pretest and posttest. The statistical test used was mixed-design ANOVA. Efficacy scale was used to determine the increase in teacher efficacy, checklist skill of verbal and non-verbal communication to determine the increase in teacher's skill and knowledge manipulation checks used to determine the increase in teacher's understanding. Twenty teachers of educated special school SLB-C P and SLB-C N in Yogyakarta were selected purposively. The result showed a comparison between the experiment and control group which have a significant difference for the skill of delivering CSA prevention (F=127, 447; p less than 0.05) and there is no significant difference for efficacy teaching CSA prevention (F=3.560; p less than 0.05). Therefore program of Jari Peri can improve the skill of delivering CSA prevention to the SLB-C teacher, but it can not improve the efficacy of teaching prevention of CSA on the teacher of SLB-C.